Profile of Spatial Ability of High School Students when Solving Geometry Problems - Wahyuni, Septia; Noviani, Julia; Saleha, Dian (SEAMEO Regional Centre for QITEP in Mathematics, 2024)
Learning geometry began in elementary school and continued through high school, as well as at more advanced levels in the area of interest of higher education. This is because studying geometry can enhance students' problem-solving skills and mathematical reasoning. Prioritized in geometry are the acquisition of spatial reasoning skills and an understanding of geometrical shapes and properties. This research aims to describe the spatial abilities of high school students in solving geometry problems. This study used qualitative research methods using descriptive design. The research subjects in this study were ten grade students in a senior high school in Aceh, Indonesia, consisting of three subjects with high, medium and low geometry abilities. Data collection techniques used were tests and interviews. The instruments in this study were geometric ability tests, spatial ability tests and interview guidelines. Data analysis techniques use data analysis techniques; data reduction, data display and draw a conclusion. The results of the study show that the spatial ability profile of students in the high and medium categories in solving geometry problems is that they have good abilities in showing correct perception of the position of geometric objects; have good ability to show correct perception of the shape of a geometric object. The low category students have good abilities in spatial perception but have poor abilities in visualization abilities. Students with high, medium and low abilities in solving geometry problems have good abilities in demonstrating mental rotation abilities.